Effectiveness of Educational Program on Nurses’ Knowledge toward Malignant Solid Tumors of Children at the Oncology Center - Qasim K. Aljobury; Zahid Jassim Mohammed; Khamees Bandar Obaid (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Solid tumor is one of the problem facing the early childhood and the common types of solidtumors are (Lymphomas, Nephroblastoma and Wilm’s Tumors)Methodology: The study was designed as quiz-experiment design (non -probability sample) using (pre andpost-test). Participants were 50 nurses working in the oncology center , and being, tested in three periodspre-test and post-test-1, and post-test-2 after applying an education program regarding improving theirknowledge toward malignant solid tumor.Results: The study outcomes low (33.3%) in assessment of nurses’ knowledge before applying theeducational program and became high in test -1 (81.24%) and in test-2 (87.93%) assessment of nurses’knowledge after applying the educational program.Conclusions: The level of knowledge regarding the solid tumor malignancy among nurses’ enrolled in thepre-test assessment of the study and control groups was low level. The educational program is an effectivein improvement of nurses’ knowledge regarding solid tumor malignancy.Recommendations: The need for educational activities to improve and update the more efforts should bedone to improve and update nursing staff knowledge.